Mysterious Interrelation: NLP and Literary Imagination - Tuhina; Dr. Shivani Vashist, (Indian Journal of Artificial Intelligence and Neural Networking (IJAINN), 2024)
This research study examines the emerging topic of investigating the combination of artificial intelligence (AI) and natural language processing (NLP) in the context of literature. The literary domain has transformed with the incorporation of AI-led NLP beings, illustrating their progression from simple tools to intricate characters wrestling with profound philosophical inquiries. This research paper will explore the burgeoning relationship between Natural Language Processing and literature, focusing on the complex intersections that shed light on the depiction of intelligent machines and the ethical dilemmas they pose in literary works. This investigation will involve multiple aspects: primarily, the depiction of NLP entities as characters within stories, analyzing their emotional complexity, development, and interactions with human protagonists through Qualitative Literature Review and Textual Analysis Methodology. Furthermore, it will examine the ethical quandaries associated with NLP, encompassing issues of autonomy, morality, and the ethical obligations inherent in their development and existence through a few case studies.